Cognitive behavioural therapy for tinnitus (Protocol) - Fuller, Thomas; Cima, Rilana; Langguth, Berthold; Mazurek, Birgit; Waddell, Angus; Hoare, Derek J.; Vlaeyen, Johan W.S. (Wiley, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects and safety of CBT for tinnitus in adults.